2022
DOI: 10.3390/cells11091395
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Wound Closure Evaluation in Skin Cell Lines after Treatment with Common Antiseptics for Clinical Use

Abstract: In recent years, new therapies, such as skin cell lines injections, have emerged to promote re-epithelialization of damaged areas such as chronic ulcers or to treat patients with severe burns. Antiseptics are commonly used during wound clinical management to avoid serious infections, but they may delay the healing process due to their apparent cytotoxicity to skin cells. The cytotoxicity of ethanol, chlorhexidine digluconate, sodium hypochlorite, povidone iodine and polyhexanide was evaluated in this in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…In both assays, cell migration in the assay of PRM6 was comparable to that of the negative control (cell culture medium) and to that of a commercial CHX-based AMD (Bactigras ® ). This result agrees with in vitro studies that show that the migration capacity of keratinocytes and fibroblasts is not affected when treated with low PHMB concentrations (0.001%) [194]. These two in vitro wound healing assays are not the most representative models of a wound.…”
Section: Biological Evaluation: Wound Healingsupporting
confidence: 88%
See 1 more Smart Citation
“…In both assays, cell migration in the assay of PRM6 was comparable to that of the negative control (cell culture medium) and to that of a commercial CHX-based AMD (Bactigras ® ). This result agrees with in vitro studies that show that the migration capacity of keratinocytes and fibroblasts is not affected when treated with low PHMB concentrations (0.001%) [194]. These two in vitro wound healing assays are not the most representative models of a wound.…”
Section: Biological Evaluation: Wound Healingsupporting
confidence: 88%
“…Depending on the concentration, PHMB may exhibit in vitro cytotoxicity [194]. In PHMB loading by soaking, a dependence of the result of the cytotoxicity evaluation on the conditions employed in the preparation of sample extracts was found in a study with the PRM7 membrane.…”
Section: Prm17mentioning
confidence: 99%
“…[ 23 ] Their MSC properties were investigated by the following experiments: Colony‐forming unit assay: hPDLSCs of 4 × 10 3 per well were inoculated in six‐well plates with 2 mL culture medium changed every 2 d. After 3 weeks, the cells were fixed with 4% PFA for 20 min and stained with 1% crystal violet for 1 h. The cell colonies consisting of more than 50 cells were observed using light microscopy (Primo Vert, Carl Zeiss, Jena, Germany). Cell‐doubling time assay: hPDLSCs of 5 × 10 5 per well were inoculated in T175 culture flasks with 20 mL culture medium changed every 2 d. After 3, 6, 9, and 12 d, the cells were collected and counted to produce a cell‐growth curve. Cell viability assay: hPDLSCs of 5 × 10 3 per well were inoculated in 96‐well plates with 0.1 mL culture medium changed every 2 d. After 1, 3, 5, and 7 d, the cell viability was longitudinally assessed by AlamarBlue HS Cell Viability Reagent as described before. [ 56 ] Osteogenic differentiation assay: hPDLSCs of 8 × 10 3 per well were inoculated in 24‐well plates with 0.5 mL culture medium. When the cells reached 80% confluence, the medium was replaced by an osteogenic medium composed of culture medium and 5% StemXVivo human osteogenic supplement.…”
Section: Methodsmentioning
confidence: 99%
“…• Cell viability assay: hPDLSCs of 5 × 10 3 per well were inoculated in 96well plates with 0.1 mL culture medium changed every 2 d. After 1, 3, 5, and 7 d, the cell viability was longitudinally assessed by AlamarBlue HS Cell Viability Reagent as described before. [56] • Osteogenic differentiation assay: hPDLSCs of 8 × 10 3 per well were inoculated in 24-well plates with 0.5 mL culture medium. When the cells reached 80% confluence, the medium was replaced by an osteogenic medium composed of culture medium and 5% StemXVivo human osteogenic supplement.…”
Section: Methodsmentioning
confidence: 99%
“…PHMB-based antiseptics introduce low tissue-toxicity, whereas other antiseptics (e.g., PVP-I and octenidine) have significant impact on cell viability 106 (although other studies have shown low cytotoxicity of HOCl to cells 107 ). Laboratory studies have shown that PHMB (or solutions containing PHMB) affect cells in a variety of ways in terms of cytotoxicity: several studies show no or low-level cell cytotoxicity 106,[108][109][110] whilst others show significant levels of toxicity to cells. 111 Kramer al (2019) 104 comparing an extensive number of antiseptics for the antibacterial activity against test organisms and assessing the cytotoxicity on cultured cells found that PHMB was one of the most suitable antimicrobial agents for use wound antisepsis.…”
Section: Broad-spectrum Efficacy Of Phmbmentioning
confidence: 99%